Pemanfaatan Benda Jaminan Atas Pembayaran Hutang Di Desa Togeme Menurut Fatwa MUI Maluku Utara - Killian, Nursinita; Ningsih, Restu Fitria; Muksin, Fitriyani (Peneliti.net, 2024)
The use of collateral utilization by the parties giving loans as a form of debt payment is a tradition carried out by Togeme village communities. The existence of an urgent need makes people take large amounts of money loans in a short time without regard to losses later, especially in debt agreements that are not in writing between the two parties. With this, the researchers studied the problem using field research methods based on the views of the Fatwa commission MUI North Maluku. The result of the research is that the traditional debt borrowing of Togeme village communities by making farmland a guarantee object in debt repayment. When it has not fulfilled the specified timeframe, the debtor cannot take the yield from the agricultural land. According to the view of the Fatwa Commission of MUI North Maluku, this tradition is permitted in Islam as long as there are no elements that destroy or cancel the rule and conditions, such as the elements of deceit, rise, and iniquity.